Role of temperature-sensitive mutants in persistent infections initiated with vesicular stomatitis virus. - Youngner, J S (1976)
Noncytocidal persistent infections at 37 C of mouse L cells (Lvsv) with infective B particles of vesicular stomatitis virus (VSV) could be established only in the presence of large numbers of defective interfering (DI) particles. Under these conditions, there was a rapid spontaneous selection of temperature-sensitive (ts) virus. At 10 days there was an increase to 17.8% in the frequency of ts clones in the virus population; by 17 days this frequency had reached 85.2%, and by 63 days 100% of the clones isolated were ts at 39.5 C, the nonpermissive temperature used. All 34 of the clones isolated from the 84-day fluid had an RNA-phenotype, and 8 clones that were tested all belonged to VSV complementation group I. When tested by an interference assay, Lvsv fluids did not contain significant numbers of DI particles (less than 1 DI/PFU). Furthermore, persistent infection of L cells at 37 C could be initiated under conditions in which few, if any, DI particles were present by using low input multiplicities (10(-4) and 10(-5) of a clonal isolate of an RNA-group I mutant obtained from Lvsv cells. On the basis of these and other results, a mechanism is proposed to explain the role of ts mutants in both the establishment and maintenance of the persistently infected state.